Konflik Organisasi di PT Garuda Indonesia: Analisis Kasus Perusahaan Penerbangan Nasional - Aprinawati Aprinawati; Imamul Khaira; Agnes Mika Cristina Br. Manik; Amanda Agustin; Ayu Triani Hutagalung (Departement of Mathematics Education, 2024)
This study aims to analyze the main causes of conflict occurring at PT Garuda Indonesia, the impact of these conflicts on the company's performance, and to provide strategic recommendations to prevent similar conflicts in the future. This research employs a qualitative method with a literature review approach, where data is collected through literature studies from various academic sources, articles, and company reports related to the conflicts that have occurred at PT Garuda Indonesia. The findings indicate that the conflicts at PT Garuda Indonesia are caused by weak internal oversight, conflicts of interest, and a lack of management transparency. The impact of these conflicts is reflected in decreased employee morale, a damaged corporate reputation, and dissatisfaction among management and shareholders. This research implies the importance of implementing good corporate governance and the need for stricter oversight systems to manage and prevent conflicts within the organization. The company is expected to improve relationships with all stakeholders through transparency and effective communication.